2017
DOI: 10.21511/imfi.14(1-1).2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Does R&D investment under corporate social responsibility increase firm performance?

Abstract: Research and development (R&D) investment affects firms' growth and reflects their investment energy. However, it is recorded as an expense in financial statements, according to generally accepted accounting principles (e.g., International Financial Statements Standards). This study examines whether firms' R&D investment has a positive effect on their performance, when they engage in corporate social responsibility. The author focuses on firms that have earned corporate social responsibility awards from Global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Several pieces of empirical evidence of a nexus between R&D investment and FFP exist. Lin (2017) found that R&D investment has a positive link with a firm's value in a study of firms engaging in social responsibility in Taiwan. Ganda (2018) reported a positive nexus between Green R&D and firm value in an analysis of 14 South African mining companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several pieces of empirical evidence of a nexus between R&D investment and FFP exist. Lin (2017) found that R&D investment has a positive link with a firm's value in a study of firms engaging in social responsibility in Taiwan. Ganda (2018) reported a positive nexus between Green R&D and firm value in an analysis of 14 South African mining companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prospector companies are aware of the urgency of sustainability issues, but managerially, they cannot be mapped and coordinated well in connection with their more dynamic business movements (Miles et al, 1978). In addition, even though there is an orientation towards RnD investment to explore new products, companies still consider financial factors due to other costs as expenses, which can impact the company's short-term financial performance (Lin, 2017).…”
Section: Environmental Performancementioning
confidence: 99%
“…Maglio (2017) stated that quality financial reports must be prepared in accordance with accounting standards. According to Whittington (2017) one of the factors that can influence the realization of quality LKPD is the competence of human resources and the application of government accounting standards, and good corporate governance (Lin, 2017;Misund, 2017). The preparation of quality financial reports must meet accounting standards and be of good quality, so that the information in the financial statements can be understood properly.…”
Section: Introduction *mentioning
confidence: 99%